An Analysis of Formal and Informal Language in Classroom Listening Comprehension of TBI 2 Students at UIN Sumatera Utara: Analisis Bahasa Formal dan Informal dalam Pemahaman Mendengar di Kelas pada Mahasiswa TBI 2 di UIN Sumatera Utara - Amelia Azzahra; Aulia Rahma; Queen Latifa Dalimunthe; Shinta Nurfidha; Deasy Yunita Siregar (KAMPUS AKADEMIK PUBLISING, 2026)
Abstract: This study analyzes the use of formal and informal language in classroom listening comprehension among second-semester students of the Tadris Bahasa Inggris (TBI) program at UIN Sumatera Utara. Listening comprehension is a crucial skill in English as a Foreign Language (EFL) learning, and students’ understanding of spoken input may vary depending on language registers used during classroom interaction. This study employed a descriptive quantitative research design involving 25 TBI 2 students selected through total sampling. Data were collected using a close-ended questionnaire distributed via Google Forms and analyzed using descriptive statistics, including frequencies and percentages. The findings indicate that most students are able to distinguish between formal and informal language used by lecturers during listening activities. Students generally perceive informal language as easier to understand, while formal language remains comprehensible and appropriate in academic contexts. Classroom interaction, intonation, and shifts in language style also support students in identifying levels of language formality. These findings suggest that a balanced use of formal and informal language may support effective listening comprehension in EFL classrooms.